Barriers to quality of work life among Bangladeshi nurses: a qualitative study. (8th August 2019) - Akter, N.; Akter, M.K.; Turale, S.
Abstract : Aim: To explore and provide understanding of the barriers to quality of work life among registered nurses in Bangladesh. Background: Globally, there is growing interest in the working environments of nurses, especially at a time of nursing shortages and with the focus on safety and care quality in health systems. In a low socio‐economic country like Bangladesh, nurses struggle in a grossly underfunded healthcare system to deliver care to the people but no studies have been conducted on their quality of work life. Methods: This qualitative descriptive study was conducted at three Bangladeshi tertiary hospitals in May 2015–January 2016. Three focus group discussions were held with 30 registered nurses exploring their perceived barriers to quality of work life. Data were analysed with content analysis. Findings: Seven barriers to their work‐life arose: heavy workloads; lack of government accommodation and transportation; poor health status; lack of support from nursing supervisors; lack of promotion opportunities; incomplete hospital policies and procedures; and lack of night shift and risk allowances. Discussion: Participants described many issues and barriers impacting on their work‐life. They perceived little reward for their hard work, felt that their health suffered from their working conditions and described a low QWL. Conclusion and policy implications: Findings provide information for nursing and health policymakers and leaders to reduce barriers to improve work‐life quality among nurses that can contribute better to quality of nursing care, and nursing retention and satisfaction. Work policies and practices, and funding and other resources need to be scrutinized to ensure better working conditions for Bangladeshi nurses. Limitations: Interviews were conducted with nurses only in tertiary hospitals in the Bangladeshi capital, and understanding of barriers to work‐life quality of nurses in other health settings and regions needs to be explored.